Б.ГЕНЖЕМУРАТОВТЫҢ АЗАМАТЛЫҚ ЛИРИКАСЫНЫҢ КӨРКЕМЛИК ӨЗГЕШЕЛИКЛЕРИ - Сагидуллаева, Ж.Н. (SCIENCE and SOCIETY, 2016)
This article is devoted to one of the most important problems of karakalpak literature study – to the learning of artistic peculiarities of civil lyrics of B.Genjemuratov. These artistic searchings are analyzed on the example of the lyrics of the poet in 1980-2000 s. In modern literary process enriching of lyrics with new artistic forms and intellectual properties by B.Genjemuratov is proved with the help of scientific and artistic analysis. The researcher reveals artistic peculiarities of civil lyrics of B.Genjemuratov with his individual style and mastery of artistic thought. Conclusions of the researcher about artistic peculiarities of the lyrics of the poet can serve as the basis to the learning of the works of individual poets, including the works of B.Genjemuratov in new scientific trends in modern karakalpak literature study.
Keywords: civil lyrics; human ideas; the position of the author; lyric hero; poetic thought; many layers of meaning; artistic punctuation; style